Imaging Modalities for Locating Impacted Maxillary Canines: A Critical Literature Review - , Marcela Maria Costa Borges, Uiara Braga dos Santos, Lúcio Mitsuo Kurita, Fábio Wildson Gurgel Costa, Diego Martins de Paula, Diego Santiago de Mendonça (Archives of Current Research International, 2025)
Aims: To do an integrative review of the literature on the types of imaging exams used to determine the position of the impacted maxillary canines (IMC), with emphasis on the analysis of panoramic radiographs (PR) and cone-beam computed tomography (CBCT). Methodology: A search was carried out on the Web of Science, PubMed, Scopus and VHL databases, which resulted in 395 articles; 42 duplicates were removed, totalizing 353 articles. After reading the titles and abstracts, 281 were excluded for not meeting the eligibility criteria. 56 articles were selected for full reading, and 5 articles were included for data synthesis. Results: The authors used PR, CBCT, periapical and occlusal radiographs, which were evaluated by orthodontists, surgeons and radiologists. Different assessments were identified regarding the position of the canine and the presence of root resorption, depending on the imaging examination. Conclusion: The possibility of identifying root resorption with PR is controversial among authors; CBCT images were considered a more accurate examination method compared to two-dimensional images.